Probabilistic modelling of engineered nanomaterial emissions to the environment: a spatio-temporal approach1. Issue 4 (30th August 2015) - Sun, Tian Yin; Conroy, Gulliver; Donner, Erica; Hungerbühler, Konrad; Lombi, Enzo; Nowack, Bernd
<x xml:space="preserve">Abstract</x> For the environmental risk assessment of engineered nanomaterials (ENM) knowledge about environmental concentrations is crucial.